Antibacerial potential of some plant extracts againts aquatic pathogens. - Ballad, Emma L. (1978)
Phytochemical screening of the dried leaves of papaya Carica papaya, avocado Persea americanaand neem tree Azadirachta indica revealed the presence of bioactive components-antraquinones, tannins, flavonoids, and saponins, which have been associated to its antibacterial properties. The antibacterial activity of the aqueous and ethanolic extracts of plant materials was tested by disk diffusion method against fish pathogenic bacteria Pseudomonas aeruginosa, Strptococcus faecalis, Staphylococcus aureus and Aeromonas hydrophila. All pure extracts displayed specific antibacterial activity in inhibiting the growth of all bacteria tested. Plant extracts were found to be effective up to 0.1 - 1 mg/ml. Antibiotic oxytetracycline (30 ug) was used as positive control while respective slvents as negative control. Results showed that ethanolic extracts were more active compared to aqueous (p<0.05). Growth of inhibition also decreases with decreasing concentration. In the 96 h acute toxicity test, plant extracts used in this study manifested toxic effect in varying degree to both Nile tilapia Oreochromis niloticus and milkfish Chanos chanos fry. A. indica leaf extracts were the most toxic to both fish. Toxic effect, however, is very low as marked by the LC 50. No significant difference were observed on the water parameters of treatment with lower concentration of extracts compared with the control. With the increase of concentrations, however, significant difference was noted but still within the acceptable range of the need of the test organisms. Treatment concentrations against bacteria were much lower than the lethal concentrations. Results from this study can be used as preliminary basis for isolation of the antibacterial agents from the agents from the plant materials and undergo pharmacological evaluation for use in fish health management.
Thesis (M. S. Fisheries - Aquaculture) - Institute of Aquaculture, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, March 2010.
Keywords: Antibacterial; Plant extract; Pathogens